Reactive blending of poly(l-lactide) and chemically-modified starch grafted with a maleic anhydride-methyl methacrylate copolymer - Ratthaphat Bunkerd (2018)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Blends of poly(l-lactide) (PLL) and chemically-modified native cassava starch (CMS) have been prepared by melt mixing and then fabricated into thin films for property testing. The CMS was prepared by copolymerizing maleic anhydride and methyl methacrylate in solution in dimethyl sulfoxide in the presence of the dissolved starch. The objective was for the poly(maleic anhydride-co-methyl methacrylate), P(MAH-co-MMA), copolymer formed to then graft onto the starch via the reaction between its anhydride groups and the hydroxyl groups of the starch. The rationale behind this chemical modification was to improve the compatibility of the starch particles with the PLL matrix via intermolecular transesterification reactions during melt blending. As a result, the enhanced interfacial adhesion between the PLL and the CMS would lead to an improvement in mechanical properties such as tensile strength and toughness compared to the PLL blended with the unmodified native starch. This paper describes some of the results from this work.